Role of sirtuin 1 (SIRT1) gene polymorphisms in pituitary adenoma development. Literature review - Morkūnaitė , G.; Glebauskienė , B.; Liutkevičienė , R. (Neurologijos seminarai, 2018)
Hypophysis is a small but important human internal gland that regulates the hormonal activity of other glands. Pituitary adenoma (PA) is one of the most common human neoplasias localised in the sphenoid area. Recently, many studies have investigated the causes of PA but the main factors that determine the appearance of PA have not yet been identified. The most important agent of tumors are genes which could determine tumor appearance. One of these factors could be the SIRT1 gene which is important for regulating the metabolic processes and has a significant effect on tumors. In this article, we will review the PA classification’s innovation, etiology, pathogenesis, SIRT1 polymorphisms and their significance for PA development.